SOME METEOROLOGICAL, HYDROLOGICAL, DYNAMICAL FEATURES IN QUY NHON BAY - Hoan, Pham Si; Cong, Nguyen Chi; Mau, Le Dinh (Vietnam Journal of Marine Science and Technology, 2014)
This paper described some features of winds, rainfall, freshwater discharge, water temperature and salinity, currents in Quy Nhon bay corresp-onding to different conditions. Data source was taken from Meteo - hydrological stations and field survey campaigns in Quynhon Bay area. Circulation patterns were computed using MIKE-21 model. The studied results show that distribution features of the above mentioned factors are corresponding to seasonal variation. Northeast (NE) Monsoon period is from November to April (strongest in December) with main directions in NNE, NE, NE (probability of about 25.1 - 53.7% and of 1.6 - 3.3 m/s). Southwest (SW) Monsoon period is from May to September (strongest in August) with main direc-tions in SE, SSE, WNW (probability of about 22 - 35.3% and with speed of less than 1.6 m/s). Variation of rainfall and freshwater discharge were similarly. There are main and auxiliary rainy stages. The main rainy stage is from September to December (strongest in early November). The aux-iliary rainy stage occurred in May, but it is irregularly. Annual rainfall variation is from 1,247 to 2,653mm. Annual river discharge varies from 41.1 to 102.2m3/s (strongest in November). Dry season period is from January to August. The salinity variation is contrary to rainfall and river discharge variation. The average monthly of surface water salinity is highest in July (about 30.1‰), and lowest in November (about 11.4‰). Water temp-erature is high from May till September. Its value is highest in June (29.8oC), and lowest in January (23.9oC). Circulation in coastal area of Quy Nhon bay is mainly formed by tides, winds and river inflow. Current is from the East boundary of Quy Nhon bay flows into the bay and towards the South during flood tide and contrary direction during ebb tide. Current velocity was generally not strong with maximum value of about 34cm/s and 30cm/s during flood and dry periods respectively. River water flows to the bay along the coastal line towards South, and other remain part of river water flows along Phuongmai peninsula coastal towards the open sea.